Evaluación de los Factores de Riesgo Psicosocial Intralaboral en una Institución de Nivel I de Atención en Salud de Arauca - Martínez Rozo, Ana Milena (Psicología, 2017)
The objective of this research was to evaluate the psychosocial risk factors in-work to which are exposed the health care and administrative staff of a health institution at level care 1 in the department of Arauca. Understanding by factors of in-work psychosocial risk as those affections that in the interior of the work deteriorates the physical and mental health of the worker generating demotivation and low productivity in the same and that affects his surroundings outside the work. It is a descriptive, cross-sectional, non-experimental research. The sample consisted of 45 workers from the care and administrative area of the institution. The participants were evaluated with the instrument created by the Ministry of Social Protection (2010), Questionnaire of psychosocial risk factors in-work, form A and B. As a result, a total score of in-work psychosocial risk factors for bosses, professionals or technicians (Form A) of Very High Risk; In terms of auxiliaries or operators (form B). The level of risk was High Irrigation. The results indicate that promotion and prevention actions should be taken in order to improve the conditions and quality of working`s life of the employees at this health institution. Therefore, they require immediate intervention under an epidemiological surveillance system.